Ethnobiological Classification in Two Indigenous Language of Chaco: Toba (Guaycuruan) and Maká (Mataco-Mataguayan) - Messineo, Maria Cristina (2011)
This article examines the linguistic devices involved in the classification of nouns referring to the plant and animal world in two languages of the Gran Chaco area: Toba (Guaycuruan) and Maká (Mataco-Mataguayan). Drawing on previous studies of nominal classification in these languages, it analyzes how derivational morphology and nominal composition are used as mechanisms in categorizing the natural world in the formation of ethnobotanical and ethnozoological lexicon. The article contributes to the typology of nominal classification in general and in particular to that of the indigenous languages of the Gran Chaco region.